Cytotoxicity and Endocrine Disruption in Materials Used for Removable Orthodontic Retainers: A Comprehensive Review - Katarzyna Chojnacka; Marcin Mikulewicz (Dentistry Journal)
Objective: To evaluate the cytotoxicity and endocrine-disrupting potential of materials used in removable orthodontic retainers. Methods: A literature search (2015–2025) covered in vitro cytotoxicity, estrogenicity, in vivo tissue responses, and clinical biomarkers in PMMA plates, thermoplastic foils, 3D-printed resins, PEEK, and fiber-reinforced composites. Results: Thirty-eight in vitro and ten clinical studies met inclusion criteria, identified via a structured literature search of electronic databases (2015–2025). Photopolymer resins demonstrated the highest cytotoxicity, whereas thermoplastics and PMMA exhibited predominantly mild effects, which diminished further following 24 h water storage. Bisphenol-type compound release was reported, but systemic exposure remained below regulatory limits. No statistically significant mucosal alterations or endocrine-related effects were reported in clinical studies. Conclusions: Retainer materials are generally biocompatible, though data on long-term endocrine effects are limited. Standardized biocompatibility assessment protocols are necessary to enable comparative evaluation across diverse orthodontic materials. Single-use thermoplastics contribute to microplastic release and pose end-of-life management challenges, raising concerns regarding environmental sustainability.